Internet QoS architectures and mechanisms for quality of service - Wang, Zheng (San Francisco : Morgan Kaufmann, 2001)
Guaranteeing performance and prioritizing data across the Internet may seem nearly impossible because of an increasing number of variables that can affect and undermine service. But if you're involved in developing and implementing streaming video or voice, or other time-sensitive Internet applications, you understand exactly what's at stake in establishing Quality of Service (QoS) and recognize the benefits it will bring to your company. What you need is a reliable guide to the latest QoS techniques that addresses the Internet's special challenges. Internet QoS is it-the first book to dig deep into the issues that affect your ability to provide performance and prioritization guarantees to your customers and users! This book gives a comprehensive view of key technologies and discusses various analytical techniques to help you get the most out of network resources as you strive to make, and adhere to, meaningful QoS guarantees. * Includes valuable insights from a Bell Labs engineer with 14 years of experience in data networking and Internet protocol design. * Details the enhancements to current Internet architectures and discusses new mechanisms and network management capabilities that QoS will require. * Focuses on the four main areas of Internet QoS: integrated services, differentiated services, MPLS (Multiprotocol Label Switching), and traffic engineering.
1 The Big Picture -- 2 Integrated Services -- 3 Differentiated Services -- 4 Multiprotocol Label Switching -- 5 Internet Traffic Engineering.
Includes bibliographical references (p. 219-223) and index.
Keywords: Internet -- Evaluation; Telecommunication -- Traffic -- Management; Electronic books